Communications as a critical factor in advanced manufacturing systems. (2nd November 2004) - Udo, Godwin J.
The dramatic advancement and the adoption of advanced manufacturing systems (AMS) in organisations can be attributed to their numerous benefits that can improve the competitive position of manufacturing firms. AMS affect not just the manufacturing but the whole company's operations, giving new challenges to a firm's ability to manage both manufacturing and information technologies. Although the benefits of AMS are numerous and have been found to have direct links with the firm's characteristics, only a handful of companies have been able to realise the full benefits of AMS. The literature is replete with the argument that some critical success factors are required for successful AMS implementation. One of these factors is effective communications prior to, during, and after AMS implementation. The purpose of this study was to investigate the extent to which communications affect the benefits of AMS. Four hundred validated questionnaires were mailed out to US manufacturing firms and 92 (23%) usable responses were received and used in this study. The findings are interesting and have some practical implications. The results show that communications have a positive significant association with all the AMS benefits considered in this study.